Cryptocurrency and the Business Cycle : a DSGE Model Approach - Křovina, Petr; Maršál, Aleš; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
This thesis investigates how a business cycle performs when cryptocurrency is demanded by the agents. Theoretical framework regarding adoption of this asset is derived. DSGE model where agents choose to hold cryptocurrency or government currency is then developed. Supply and demand for the latter is endogenous. We find agents demand lower real holdings of government currency and cryptocurrency in response to a positive preference shock. They increase demand for both currencies when subject to a positive technology shock. Monetary policy shock induces a substitution effect where agents demand cryptocurrency at the expense of government currency. Furthermore, agent’s demand for government currency is more volatile when cryptocurrency is not present in the model.
Vedoucí práce: Aleš Maršál
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses